Cellular and Deafness Mechanisms Underlying Connexin Mutation-Induced Hearing Loss – A Common Hereditary Deafness - Wingard, Jeffrey C.; Zhao, Hong-Bo (Frontiers in Cellular Neuroscience, 2015)
Hearing loss due to mutations in the connexin gene family which encodes gap junctional proteins is a common form of hereditary deafness. In particular, connexin 26 (Cx26, GJB2) mutations are responsible for 50% of nonsyndromic hearing loss, which is the highest incidence of genetic disease. In the clinic, Cx26 mutations cause various auditory phenotypes ranging from profound congenital deafness at birth to mild, progressive hearing loss in late childhood. Recent experiments demonstrate that congenital deafness mainly results from cochlear developmental disorders rather than hair cell degeneration and endocochlear potential (EP) reduction, while late-onset hearing loss results from reduction of active cochlear amplification, even though cochlear hair cells have no connexin expression. Moreover, new experiments further demonstrate that the hypothesized K+-recycling disruption is not a principal deafness mechanism for connexin deficiency induced hearing loss. Additionally, there is no clear relationship between specific changes in connexin (channel) functions and the phenotypes of mutation-induced hearing loss. Cx30, Cx29, Cx31, and Cx43 mutations can also cause hearing loss with distinct pathological changes in the cochlea. These new studies provide invaluable information about deafness mechanisms underlying connexin mutation induced hearing loss and also provide important information for developing new protective and therapeutic strategies for this common deafness. However, the detailed cellular mechanisms underlying these pathological changes and pathogeneses of specific-mutation induced hearing loss remain unclear. Finally, little information is available for humans. Further studies to address these deficiencies are urgently required.